Aspects of the breeding biology of Bewick’s Swans Cygnus columbianus bewickii nesting in high densities in the Chaun River delta, Chukotka, east Russia - Solovyeva, Diana; Vartanyan, Sergey (Wildfowl, 2014)
The breeding biology of Bewick’s Swans Cygnus columbianus bewickii nesting on Ayopechan Island in the Chaun River delta, Chukotka, northeast Russia was monitored from 2002–2013 inclusive, which coincided with a marked increase in the number of swans in the Eastern Population. A total of 535 nests were located during the study, and nest density, clutch size, egg dimensions, earliest hatch dates and nest success (i.e. whether at least one egg hatched) were recorded. Average nest density was 2.07 ± 0.25 nests/km2 (range = 0.98–3.33 nests/km2) and nest density appeared to increase over the study period, although the trend was not statistically significant. The minimum distance between two swan nests was 82 m, and average clutch size was 3.60 eggs (s.d. = 1.05; range = 1–7 eggs, n = 410 clutches). Nest success, recorded in 2009–2013, ranged from 32.2–72.2% and averaged 46.5%. Weather variables, such as the date on which temperatures rose above zero, the timing of snow melt, late May and early June temperatures, and a general (integrated) measure of spring weather conditions, were not significantly associated with nest density. Mean clutch size decreased during the study, through there being a decreasing proportion of large clutches of 5 and 6 eggs. Results are discussed in relation to a separate study of the breeding biology of Bewick’s Swans in the Northwest European Population, which increased in numbers between the mid 1970s and the mid 1990s but is currently in decline.